Analysis of 3D Printing Applications with ABS Filament Material for Designing Unmanned Aircraft Bodybuils - Lazuardi, Lazuardi; Akhlis Rizza , Muhammad; Hadi Susilo, Sugeng; Maryono , Maryono (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
This research applies 3D printing technology using ABS filament material in designing the body of an unmanned aircraft. A quantitative approach to the simulation results is used to highlight the technical superiority of unmanned airframes. The analysis includes aspects such as structural strength. These findings provide deep insight into the potential application of 3D printing technology in the aerospace industry, as well as its application to the design, production costs and performance of unmanned aircraft. The research results show that the use of 3D printing with ABS filament has the potential to produce a strong and light aircraft body. From the research, it was found that the ideal layer thickness parameter of 0.1 to 0.2 mm does not exceed half the size of the nozzle diameter of 0.4 mm to produce fine raster fibers on the aircraft body without a crew. From the research it was found that the ideal speed parameter for printing the aircraft body frame unmanned aircraft with ABS filament material at a speed of 30 mm/s to 50 mm/s to produce a stable raster fiber size on the aircraft body and the percentage parameter of a good fill for printing the body frame of an unmanned aircraft is at a value of 20% up to 40%. The research results found the best printing parameters for printing aircraft frames with the parameter formula of 0.15mm 3D layer height, 20% gyroid infill, with a speed of 30mm/s maximum tensile strength reaching 30.7 MPa. By considering the challenges and opportunities associated with the use of 3D printing technology, this research provides a solid foundation for further development in designing and producing unmanned aircraft bodies efficiently and innovatively.